2017
DOI: 10.3390/ma10040334
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate Bioceramics: A Review of Their History, Structure, Properties, Coating Technologies and Biomedical Applications

Abstract: Calcium phosphate (CaP) bioceramics are widely used in the field of bone regeneration, both in orthopedics and in dentistry, due to their good biocompatibility, osseointegration and osteoconduction. The aim of this article is to review the history, structure, properties and clinical applications of these materials, whether they are in the form of bone cements, paste, scaffolds, or coatings. Major analytical techniques for characterization of CaPs, in vitro and in vivo tests, and the requirements of the US Food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
590
0
23

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 793 publications
(627 citation statements)
references
References 810 publications
(1,241 reference statements)
14
590
0
23
Order By: Relevance
“…Coatings 2017, 7,182 The AFM images are given in Figure 8. It was found that the mean value of the average surface roughness Ra of the pristine mPE-nHA film and 24 h Aloe vera dip-coated mPE-nHA film surfaces were 1.17 and 7.52 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coatings 2017, 7,182 The AFM images are given in Figure 8. It was found that the mean value of the average surface roughness Ra of the pristine mPE-nHA film and 24 h Aloe vera dip-coated mPE-nHA film surfaces were 1.17 and 7.52 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our developed membrane showing enhanced blood compatibility might favor osteoblast cell proliferation for new bone tissue growth. Coatings 2017, 7,182 material, since the percentage of damage falls below two percent. Selvakumar et al [27] prepared a nanocomposite based on polyurethane incorporated with polypropylene glycol (PPG)-warped hydroxyapatite for bone tissue engineering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, and induce negative charge on composites' surfaces. This process proceeds through spontaneous reactions contain precipitation, nucleation, and growth of apatite layers on the surface of the composite [12][13][14][15]. Figure 4 demonstrates the representative XRD of Ti-HA composite before and after immersion in the SBF for various periods of time.…”
Section: Methodsmentioning
confidence: 99%
“…The solution to this problem lies in creating a coating on implant surface with biological active layer, which can significantly improve the fixation properties and prevent implant failure [4]. Calcium phosphate (CP) bioceramics as a basic mineral part of connective tissue has been extensively used in various field of biomedical applications thanks to good bioactivity, osseointegration and osteoconductive properties [5]. Despite of excellent biological properties, the CPs are known as materials with low mechanical strength and toughness, which allow their use only as filling materials or coatings.…”
Section: Introductionmentioning
confidence: 99%